A scientist-practitioner approach to an on-field assessment of mental skills in collegiate soccer student-athletes. Issue 3 (3rd July 2018) - Shipherd, Amber M.; Basevitch, Itay; Filho, Edson; Gershgoren, Lael
ABSTRACT: Sport psychology practitioners frequently utilize questionnaires to evaluate sport psychology services, yet questionnaires may not be valued as highly by the coaches and/or athletes themselves. Therefore, an alternative, more reliable, and ecologically valid method of assessing mental skills is needed for sport psychology practitioners. As such, the purpose of this article is to illustrate how an authentic field-based mental skills program assessment was used in the off-season for collegiate soccer teams. Following discussions between the sport psychology practitioners and coaching staff, pre- and post-test activities were developed and implemented on an outdoor soccer field, which was determined to be a more authentic "real-world" environment. Activities evaluated situational and tactical awareness, on-field communication, shooting self-efficacy, and performance under pressure and fatigue. The field assessment experience provided a good method for the sport psychology practitioners to observe improvements in mental skills, and the student-athletes and coaches reported that the activities and debrief demonstrated the involvement of mental skills in every aspect of their soccer performance.